2006
DOI: 10.1001/archpsyc.63.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lower-Cost Incentives on Stimulant Abstinence in Methadone Maintenance Treatment

Abstract: An abstinence incentive approach that paid 120 dollars in prizes per participant effectively increased stimulant abstinence in community-based methadone maintenance treatment clinics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
290
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(297 citation statements)
references
References 37 publications
5
290
1
Order By: Relevance
“…However, the 100 mg/day dose is generally considered adequate for most patients, and it is higher than that used in other trials of CM in methadone-maintained populations. For example, the approximate mean methadone doses were 70 mg/day in Petry and Martin (2002), 86 mg/day in Peirce et al (2006), 50-70 mg/day in Epstein, Hawkins, Covi, Umbricht, and Preston (2003), and 65-85 mg/day in Schottenfeld et al (2005). These studies showed significant decreases in cocaine and/or opiate use at the doses tested.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, the 100 mg/day dose is generally considered adequate for most patients, and it is higher than that used in other trials of CM in methadone-maintained populations. For example, the approximate mean methadone doses were 70 mg/day in Petry and Martin (2002), 86 mg/day in Peirce et al (2006), 50-70 mg/day in Epstein, Hawkins, Covi, Umbricht, and Preston (2003), and 65-85 mg/day in Schottenfeld et al (2005). These studies showed significant decreases in cocaine and/or opiate use at the doses tested.…”
Section: Discussionmentioning
confidence: 89%
“…Our patients in the high-density contingent group received prizes worth on average only $286 during the 12-week intervention, less than the cost of commonly studied voucher-based CM procedures (Downey, Helmus, & Schuster, 2000;Higgins, Badger, & Budney, 2000;Piotrowski et al, 1999;Robles et al, 2000;Silverman et al, 1996). Thus, our procedure may be more amenable to implementation in community-based settings (Peirce et al, 2006;Willenbring, Hagedorn, Postier, & Kenny, 2004).The clinical significance of our results is underscored by the finding that, in the contingentreinforcement groups, there were significantly more patients in remission of DSM-IV diagnoses of cocaine dependence at the end of treatment and during the 3 and 6 months postdischarge follow-up periods compared with yoked control participants receiving prize draws irrespective of drug abstinence. This suggests that decreases in problems associated with cocaine use persisted after treatment ended in the contingent groups.…”
mentioning
confidence: 99%
“…Study results demonstrated a reduction in stimulant use for all groups; CM produced significantly increased retention and reduced stimulant use during the treatment period, although there was no difference between the groups at follow-up. Peirce et al [19] randomised 388 methamphetamine users enrolled in methadone maintenance treatment (MMT) to usual care with or without incentives for 12 weeks. Usual care consisted of MMT and individual and group counselling as required by the clinic, in this sample up to three times a week.…”
Section: Contingency Managementmentioning
confidence: 99%
“…Findings from these clinical trial protocols are now in press. They showed that the contingency management techniques tested in the CTN were associated with a greater likelihood of stimulant-free and alcohol-free urine tests and of multiple consecutive clean urines in methadone settings (Peirce et al, 2006), and they improved both drug use and retention in outpatient "drug-free" settings (Petry et al, 2005). Dissemination materials are now being developed by ATTCs for distribution to the field at large, and at least one case study documenting the successful adoption and adaptation of these techniques in a large hospital system as a result of CTN exposure has been published (Kellogg et al, 2005).…”
Section: Voucher-based Motivational Incentivesmentioning
confidence: 99%